Prediksi Kebangkrutan Dengan Metode Springate Score (Studi Kasus Pada PT Mutiara Cintanami Sejahtra) - Prayoga Romin Syaputra; Ahmad Tomu (Journal of Financial and Tax, 2021)
In general, bankruptcy is defined as the company's failure to carry out operations to achieve its goals. The purpose of this research is to find out the potential for bankruptcy at PT Mutiara Cintanami Sejahtra. The research method used is descriptive method. The type of data used is quantitative and qualitative data. Data collection techniques are with documentation. The analysis tool used is Springate Score analysis. The Formula Springate Score: 1.03X1 + 3.07X2 + 0.66X3 + 0.4X4. The results showed that PT Mutiara Cintanami Sejahtra is in good health